1978
DOI: 10.1515/znc-1978-9-1038
|View full text |Cite
|
Sign up to set email alerts
|

Notizen: Quantification and Localisation of SH-Groups in Human Blood Serum Proteins

Abstract: The thiol groups of human blood serum proteins were determined after 24 hours interaction with dithionitrobenzoicacid (DTNB) to an average of 538 ± 60 µmol/l serum. After treatment of the serum with [35S]DTNB , autoradiograms of the protein elpherograms revealed two main peaks: The first with 63% of total activity, in the albumin region, corresponding to 0.60 SH/mol, the second with 23% of total activity, in the 7-globulin range, corresponding to 2.2 SH/mol. After 30 minutes incubation with D TNB , or with p-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1982
1982
2004
2004

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…We have previously reported that human IgG contains definite and consistent numbers of free sulfhydryl (SH) groups and labile disulfide bonds (SS*) that are detectable by disulfide exchange reaction with 5,5'-dithio-2,2'-dinitrobenzoic acid (dithionitrobenzoate; DTNB) [1][2][3][4]. In vestigations with purified subclass proteins revealed IgGl to carry 1 SS*/mol, whereas 1 SH could be assigned to the IgG2 molecule [3].…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported that human IgG contains definite and consistent numbers of free sulfhydryl (SH) groups and labile disulfide bonds (SS*) that are detectable by disulfide exchange reaction with 5,5'-dithio-2,2'-dinitrobenzoic acid (dithionitrobenzoate; DTNB) [1][2][3][4]. In vestigations with purified subclass proteins revealed IgGl to carry 1 SS*/mol, whereas 1 SH could be assigned to the IgG2 molecule [3].…”
Section: Introductionmentioning
confidence: 99%
“…In earlier communications [1][2][3] we studied the in teraction of human serum IgG with 5,5'-dithio(2,2'-dinitro)benzoic acid (DTNB) for determination of both free SH groups and labile S-S bonds. Using this method, consistent values were found in IgG from healthy persons for free SH groups (0.24 ± 0.02/mol IgG) detectable after 30 min reaction with DTNB.…”
Section: Introductionmentioning
confidence: 99%